Pengembangan Bahan Ajar Interaktif Berbantuan Flipbook untuk Meningkatkan Hasil Belajar - Salzabila, Putri Alicia; Fathurrahman, Moh. (Jurnal Penelitian Pendidikan IPA, 2024)
SD 2 Mlati Lor Kudus has important problems in learning activities, including limited digital learning media so that student learning outcomes are relatively low, especially in science education material regarding style and its influence in everyday life. This research aims to develop products, test the effectiveness and feasibility of implementing interactive learning media for teaching materials in class IV natural education and social science subjects at SD 2 Mlati Lor Kudus-Central Java. This research applies research and development (RnD) using the ADDIE research model design. This research produced four things, including: 1) Development of flipbook-based digital teaching materials on science learning style material; 2) The students response to the interactive media flipbook-based digital teaching materials was very valid with a score percentage of 93.5%; 3) Media product feasibility test which is considered very valid by experts with an average final validation of 90%; 4) The t-test results showed SIG (2-tailed) 0.00 < 0.05, indicating an increase in the average results before and after treatment on small-scale tests and large-scale tests, so it can be concluded that flipbook-based digital teaching materials have succeeded in improving student learning outcomes in fourth grade elementary school student style material subjects (science and social studies).